A Novel Neural Network Cell Method for Solving Nonlinear Electromagnetic Problems (Adv. Theory Simul. 12/2021). Issue 12 (7th December 2021) - Zhu, Gaojia; Li, Longnv; Fu, Weinong; Xue, Ming; Liu, Tao; Zhu, Jianguo
Abstract : Numerical‐Intelligent Coupled Model for Nonlinear Problems In article number 2100216, Longnv Li and co‐workers propose a NNCM coupling neural network (NN) and cell method (CM) for the effective calculation of nonlinear electromagnetic fields in ferromagnetic regions. The NNCM model the nonlinearities with partially connected NNs and construct the linearities through CM to guarantee both the training and the computing efficiencies.